Taxation and Global Spillovers in the Digital Advertising Market. Theory and Evidence from Facebook - Andrea Lassmann; Federica Liberini; Antonio Russo; Ángel Cuevas; Rubén Cuevas (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the effects of taxation on the international online advertising market, using data on Facebook ad prices, Facebook users product preferences and international trade. Our data encompass a de facto increase in the platform's corporate tax rate in several countries. We show that, due to international trade linkages, tax changes produce global spillovers. Yet, advertisers experience higher prices in countries that directly face the tax increases compared to advertisers in countries that do not. This result is consistent with a theoretical model, which shows that the platform reduces the supply of ads to advertisers from countries where taxation increases.
Keywords: H22; H25; F23; 330; tax incidence; online advertising; Facebook